أعراف الزواج في مينانجكاباو في إندونيسيا: دراسة فقهية تقويمية - Abdul Hakim Ahmad Zawawi (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
This research studies marriage customs in Minangkabau, Indonesia and the relationship between the Minangkabau people and Islamic law. The research adopts the inductive method for collecting data from books on customs, fiqh sources and research papers. The analytical method was also utilized for evaluating customs that violate Shari 'a. Interviews were conducted with experts on Indonesia, particularly about the Minangkabau people. The research concludes that marriage customs in Minangkabau hold a theory that considers custom to be based on Shari'a. Therefore, Shari'a is binding and custom is related to it. At the practical level, however, the situation is different. Some customs are considered superior to Shari'a because of the matriarchal system that has a great impact on Minangkabau culture. Examples of customs that run contrary to Shari'a are the forced exogamy, exchanging rings, husbands are inferior to their wives (e.g. In inheritance, the husbands lose the big share in favour of wives and children bear the name of mother's tribe).